Silicon homo-hetero junction solar cell: An analytical approach for modeling and characterization of the amorphous/crystalline silicon heterostructure. (August 2021) - Bashiri, Hadi; Azim Karami, Mohammad; Mohammad Nejad, Shahram
Highlights: An analytical model is investigated to model HHJ-silicon solar cells. The (p + )c-Si and (n + )c-Si buffer layers in improve SHJ solar cell performance. Buffer layers can repels free carriers from c-Si/a-Si:H interface. Sensitivity of the output parameters to interface defect density is reduced. Overall efficiency is increased by using of buffer layers. Abstract: In this paper, an analytical model is presented to study the physical aspects and properties of a novel silicon solar cell structure consisting of both heterojunction and homojunction at the front and back surfaces. The front surface stack consists of (p + )a-Si:H/(i)a-Si:H/(p + )c-Si/(n)c-Si layers and the back surface stack consists of (n + )a-Si:H/(i)a-Si:H/(n + )c-Si/(n)c-Si layers. The analytical model for electrical field, and surface potential in a-Si:H/c-Si interfaces is validated by numerical simulations. The impact of doping concentration and thickness of the buffer layers, density of states in interface defects and in the bulk of a-Si:H layers, is investigated, using the developed model. The results show that using a 10 nm thick (p + )c-Si with doping concentration of 1 × 10 19 cm - 3, the electric field increases approximately twice in the front surface of (n)c-Si. Also similar results is obtained for the back surface interfaces, and 70% increase in electric field is obtained using a 10 nm (n + )c-Si layer with doping concentration of 1 × 10 19 cm - 3 . It is shown analytically that due to field passivation enhancement on both solar cell's surfaces using the buffer layers can reduce the sensitivity of surface potential to interface defect densities. The model describes increasing field effect passivation and less sensitivity of surface potential to interface defect densities as the main elements in boosting the solar cell performance.